Energy deposition measurements of single 1H, 4He and 12C ions of therapeutic energies in a silicon pixel detector - Gehrke, Tim; Burigo, Lucas Norberto; Aricó, Giulia; Tessonnier, Thomas; Mairani, Andrea; Martišíková, Mária (Journal of Instrumentation, 2017)
In the field of ion-beam radiotherapy and space applications, measurements of the energy deposition of single ions in thin layers are of interest for dosimetry and imaging. The present work investigates the capability of a pixelated detector Timepix to measure the energy deposition of single ions in therapeutic proton, helium- and carbon-ion beams in a 300 μm-thick sensitive silicon layer. For twelve different incident beams, the measured energy deposition distributions of single ions are compared to the expected energy deposition spectra, which were predicted by detailed Monte Carlo simulations using the FLUKA code. A methodology for the analysis of the measured data is introduced in order to identify and reject signals that are either degraded or caused by multiple overlapping ions. Applying a newly proposed linear recalibration, the energy deposition measurements are in good agreement with the simulations. The twelve measured mean energy depositions between 0.72 MeV/mm and 56.63 MeV/mm in a partially depleted silicon sensor do not deviate more than 7% from the corresponding simulated values. Measurements of energy depositions above 10 MeV/mm with a fully depleted sensor are found to suffer from saturation effects due to the too high per-pixel signal. The utilization of thinner sensors, in which a lower signal is induced, could further improve the performance of the Timepix detector for energy deposition measurements.
Im Titel sind die Zahlen 1, 4 und 12 hochgestellt
Gesehen am 25.04.2018